The Influence of Social Media Influencer and Electronic Word of Mouth Mediated By Brand Image on Purchase Intention at Eternamoore Beauty Clinic Makassar - Markiones, Sartika Aprilia; Buyung Romadhoni; Andi Mappatompo (Dinasti Publisher, 2023)
This article investigates the effect between social media influencer and electronic word of mouth mediated by brand image on purchase intention at Eternamoore Beauty Clinic Makassar through descriptive-quantitative research. We test the hypotheses of 117 respondents from Eternamoore’s Instagram followers and used the Structural Equation Modelling with PLS. The result reveal that social media influencer exhibit better for brand image. Electronic word of mouth has significant and positive effect on brand image. Whereas the social media influencer has unsignificant effects on purchase intention, brand image mediates this effect. Electronic word of mouth can enhance purchase intention. Additionally, the moderated mediation analysis result revealed that the indirect effect of electronic word of mouth on purchase intention is positively moderated by brand image. These results provide a better understanding of the influencer and e-WOM and offer important contribution to the social media marketing and add valuable insights for practitioners to advance the use of Influencers and e-WOM.